Nasopharynx Recurrent Disease Prevention in Children with Lymphopharyngeal Ring Hyperplasia - V.Yu. Tkachenko; L.S. Ovcharenko (Zaslavsky O.Yu., 2016)
Bsckground. Nasopharyngeal lymphoid tissue is one of the places of accumulation and growth of respiratory disease pathogens. The most vulnerable for them are the children of preschool age with lymphopharyngeal ring hyperplasia who have been found to have the upper respiratory tract recurrent diseases. Objective. The optimization of acute rhinosinusitis treatment program in children with lymphopharyngeal ring hyperplasia. Materials and methods. We observed 120 patients aged between 3 and 6 years old, randomly distributed into 2 groups of 60 children each. Application mode: one injection into each nostril twice a day. 3% sodium chloride was applied in the form of nasal irrigations in children of the first group four times per day. Sodium chloride 0.9% was used in children of the second group by the same scheme. Clinical evaluation method consisted of anamnesis, clinical picture, general clinical research methods. Smear for cytomorphological analysis of the nasal mucosa was taken. The preparations were stained by Giemsa, the quantification of secretory sIgA in saliva was assessed by ELISA. The results were processed by the Mann - Whitney test, Fisher's exact test. Results: the use of sodium chloride 3% in the form of nasal irrigations provided statistically significant and sanation regenerating effect on the nasal mucosa. Using a 3% sodium chloride in contrast to use of sodium chloride 0.9% decrease is not accompanied by a saliva secretory sIgA levels and it leads to some increase. Conclusion. Using 3% sodium chloride nasal irrigations prevent nasopharynx recurrent disease in children with lymphopharyngeal ring hyperplasia and has a complex action in comparison with the use of 0.9% sodium chloride.